Peran Self Efficacy, Modal Usaha dan Lingkungan Keluarga Terhadap Minat Berwirausaha Mahasiswa dengan Pengetahuan Akuntansi Sebagai Variabel Moderasi - Melania Iviola Lombo (Yayasan Literasi Ilmiah Indonesia, 2023)
This research aims to prove the moderating influence of accounting knowledge on self-efficacy, business capital, and family environment on interest in entrepreneurship. The research took samples from Accounting Study Program students at several campuses in the Special Region of Yogyakarta. The primary data obtained in this research are the results of questionnaires obtained from respondents and then processed using SPSS with multiple linear regression analysis. The results of the research show that there is a positive and significant influence of self-efficacy on interest in entrepreneurship with a significance value smaller than 0.05, namely 0.000, there is a positive and significant influence of business capital on interest in entrepreneurship with a significance value smaller than 0.05, namely 0.008, there is an influence positive and significant family environment on interest in entrepreneurship with a significance value of less than 0.05, namely 0.014, and there is a positive and significant relationship between the accounting knowledge variable moderating self-efficacy, business capital and family environment on interest in entrepreneurship.